Avaliação da atividade da silimarina nanoencapsulada frente a enzimas colinérgicas - Souza, Daniela Cristina de (2022)
Silymarin is a complex mixture of bioactive compounds characterized as flavonolignans, extracted from the seeds and fruit of the plant Silybum marianum belonging to the Asteraceae family which is native to the Mediterranean region. Silymarin has antioxidant, antiinflammatory and antiviral properties, attenuating the side effects of oxidative stress through the elimination of free radicals, participating in protein synthesis. It has also been used for the treatment of chronic hepatitis and cirrhosis. However, several studies demonstrated that the components present in silymarin have low solubility in aqueous and low oral bioavailability, resulting in a limitation in its use as an antioxidant. The solid dispersion nanoencapsulation technique is known to protect bioactive compounds from unfavorable environmental conditions, in addition to increase its bioavailability and stability. Thus, the objective of this work was to produce and characterize silymarin nanoparticles obtained by solid dispersion and encapsulated with the Poloxamer 407 polymer, and also to evaluate the in vitro and ex vivo activity, through tissue homogenized Drosophila melanogaster flies, silymarin and silymarin nanoparticles against the cholinergic enzyme acetylcholinesterase (AChE) and butyrylcholinesterase (BChE). The nanoparticles were characterized by Differential Scanning Calorimetry (DSC) and Fourier Transform Infrared Spectrophotometry (FTIR), Dynamic Light Scattering (DLS) and Zeta Potential analyses. The characterization techniques showed that silymarin was efficiently encapsulated in the polymeric matrix, and through UV-VIS it could be observed that there is no evidence of degradation of the compounds present in the nanoparticles. The results obtained for the activity of the enzyme AChE and BChE in vitro, showed that silymarin and nanoparticles have the capacity to inhibit cholinergic enzymes, showing better results for free silymarin when solubilized in ethanol, confirming the hydrophobic nature of compound. The nanoparticles enabled the solubility of silymarin in water, allowing the compound to inhibit the activity of enzymes. Finally, silymarin showed no toxicity to Drosophila melanogaster when evaluated by the survival test.